Perancangan Aplikasi “Dunia Hewan” untuk Pembelajaran Anak Usia Dini Berbasis Android - Danang Respati Setyabudi; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
The technological development are rapidly growing. Various kinds and types emerge everyday smartphone at an affordable price. One of the most popular smartphones today is Android. The author hopes that this application will be beneficial and useful for anyone who uses, especially for early childhood. This educational application is designed using the Eclipse IDE and the Android SDK where the programming language used is Java programming language. In the Eclipse IDE there are emulators that can be used to see the results of the application program that has been made before running in the actual Android device. Stages of development of the software used is the SDLC (Software Development Life Cycle) by using the waterfall method and modeling software used is the UML (Unified Modeling Language). Results of this research is the realization of the android- based animal world educational applications for early childhood. Applications can runs well on devices with Android operating system at least version 2.3 (Gingerbread) with available storage space of 10 MB. Buttons and function menus within the application has been running well according to the respective functionality. The animal world educational applications can now be used for the media to learn about the world of animals, especially for early childhood android users.